Rediscovering Art Exhibition Artefacts of Indonesia Pavilion at Osaka Expo’70 Japan - Sayahdikumullah, Dikdik; Anai, Miyuki (Badan Riset dan Inovasi Nasional (BRIN), 2025)
This study traces the art exhibition artefacts that bridge tradition and modernity in the Indonesian Pavilion at the 1970 Osaka Expo in Japan. This international art exhibition project is under the responsibility of the Indonesian National Committee for Expo'70. The arrangement of the pre-presentation works of this exhibition reflects the complex correlation between the pavilion design concept, exhibition materials, and the narrative of Indonesian modern art history. A comprehensive research effort is needed to reconstruct traditional and modern art artefacts, focusing on the role of artistic think tanks in collecting their exhibition materials. Qualitative empirical methods were employed, including site location observations, data collection, literature studies, interviews, and the pavilion space reconstruction. This paper reveals that the decision to conceptualize the exhibition materials was made top-down by the National Committee for Expo'70 to the Design Center ITB (DCITB). This pivotal artistic think tank selected, designed, and implemented the configuration of various traditional and modern works of art to stand for the spirit of universalism from the perspective of Indonesia to the international world.